2015
DOI: 10.3390/ijms17010019
|View full text |Cite
|
Sign up to set email alerts
|

Stable Expression of Basic Fibroblast Growth Factor in Chloroplasts of Tobacco

Abstract: Basic fibroblast growth factor (bFGF) is a multifunctional factor in acceleration of cell proliferation, differentiation and transference, and therefore widely used in clinical applications. In this study, expression vector pWX-Nt03 harboring a codon-optimized bFGF gene was constructed and introduced into the tobacco chloroplasts by particle bombardment. After four rounds of selection, bFGF was proved to integrate into the chloroplast genome of regenerated plants and two of four transgenic plants were confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…In vitro assays of inserted genes with several synonymous codons show that translation efficiency does not always correlate with codon usage in plastid mRNAs (Nakamura and Sugiura, 2007), but they have been used in several codon optimization studies (Lutz et al, 2001;Ye et al, 2001;Franklin et al, 2002;Lenzi et al, 2008;Jabeen at al., 2010;Madesis et al, 2010;Gisby et al, 2011;Wang et al, 2015b;Boehm et al, 2016;Nakamura et al, 2016). While some studies achieved significant increases in expression (75-to 80-fold) after codon optimization (Franklin et al, 2002;Gisby et al, 2011), other studies observed negligible enhancement (Ye et al, 2001;Lenzi et al, 2008;Daniell et al, 2009;Wang et al, 2015b;Nakamura et al, 2016).…”
mentioning
confidence: 99%
“…In vitro assays of inserted genes with several synonymous codons show that translation efficiency does not always correlate with codon usage in plastid mRNAs (Nakamura and Sugiura, 2007), but they have been used in several codon optimization studies (Lutz et al, 2001;Ye et al, 2001;Franklin et al, 2002;Lenzi et al, 2008;Jabeen at al., 2010;Madesis et al, 2010;Gisby et al, 2011;Wang et al, 2015b;Boehm et al, 2016;Nakamura et al, 2016). While some studies achieved significant increases in expression (75-to 80-fold) after codon optimization (Franklin et al, 2002;Gisby et al, 2011), other studies observed negligible enhancement (Ye et al, 2001;Lenzi et al, 2008;Daniell et al, 2009;Wang et al, 2015b;Nakamura et al, 2016).…”
mentioning
confidence: 99%
“…The vector pWYP21406 was transformed into the tobacco chloroplasts by using the biolistic particle bombardment as described previously 40 . The leaves of one-month-old tobacco seedlings were used as explants, the plasmid pWYP21406 was coated with 0.66 µm gold particles, and the bombardment was carried out at 1100 psi with a shooting distance of 6 cm and a vacuum of 28 on MS medium.…”
Section: Chloroplast Transformation and Generation Of Transplastomic ...mentioning
confidence: 99%
“…However, expression of hFGF21 in plant chloroplast is not yet reported, although a member of the FGFs family, bFGF (FGF2) has been demonstrated to be successfully expressed in tobacco chloroplasts 40 . In this paper, the successful expression of hFGF21 fused to GFP at a high level (12.44 ± 0.45% of TSP) in tobacco chloroplasts is rstly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Basic fibroblast growth factor (bFGF) accelerates cell proliferation and differentiation and hence possesses wide clinical applications. A codon-optimized bFGF gene was transformed to tobacco chloroplasts, and recombinant protein accumulation was observed (Wang et al 2015). Serum antibodies developed in hemophilia B patients against coagulation factor IX (FIX) is highly challenging to eliminate due to nephrotic syndrome after continued infusion.…”
Section: Plastid Bioreactors For Molecular Farmingmentioning
confidence: 99%